Exploring social-ecological dynamics of a coral reef resource system using participatory modeling and empirical data. (April 2017) - Leenhardt, Pierre; Stelzenmüller, Vanessa; Pascal, Nicolas; Probst, Wolfgang Nikolaus; Aubanel, Annie; Bambridge, Tamatoa; Charles, Mahé; Clua, Eric; Féral, François; Quinquis, Bran; Salvat, Bernard; Claudet, Joachim
Abstract: Coral reef resource systems are complex adaptive social-ecological systems providing vital and valuable ecosystem services for human societies such as food provision, coastal protection and recreational activities. Their sustainability is questioned in many places around the world as they experience combined effects of multiple chronic anthropogenic and natural drivers at local to global scales. From a management perspective, there is a crucial need to understand how the impact of these drivers cascade through the social-ecological system components. This study develops a transdisciplinary and participatory approach to investigating the social-ecological dynamics of a Polynesian coral reef coastal system. A preliminary conceptual model using the Driver-Pressure-State-Impact (DPSI) framework is first being built through participatory modeling workshops. Then, pressure-state relationships are assessed with the help of empirical datasets as a first step towards the validation of the DPSI model. Results shows striking social-ecological interactions with different patterns in the lagoon and in the fore reef. Local management should be: (1) less resource-focused to account more specifically to the existing typology of actors; (2) more spatially-explicit to better distinguish management objectives and actions for the lagoon and the fore reef sub-systems; and (3) more coordinated with terrestrial agencies for a coherent land-sea connection and integration that would both (i) account for existing land-sea interactions and (ii) better reflect the Polynesian cultural heritage that considers nature from ridge to reef as a whole. Such conceptual models of social-ecological systems are a useful tool to build exploratory scenarios to ultimately support planning decision-making processes. Highlights: A transdisciplinary approach was developed to investigate coral reef social-ecological dynamics. A conceptual model was developed using the Driver-Pressure-State-Impact (DPSI) framework. The DPSI model was built was through participatory modeling and empirical datasets. Results showed different interactions and social-ecological patterns in the lagoon and in the fore reef.